Risks faced by Agrobank Berhad in managing the business of banking / Siti Norain Mat Zim - Mat Zim, Siti Norain (2012)
Risk is an integral part of business. Risk is any events or possibility of an event which can impair corporate earnings or cash flow over short, medium or long term horizon. The risk will affect an organization performance nowadays or in the future. All organizations deal with risks, though the nature and magnitude may differ for each type of organization. They act as financial intermediaries in any economic system. Since they help in credit creation by means of loans and advances, they faced many risk. This risk may affect the Agrobank performance and customer convenience towards it. According to this problem, this study was done, where the main purpose is to observed whether the risk manage by Agrobank has relationship with risk occurred in that organization. This study was conducted at Agrobank Berhad. Four variables were developed which are credit risk, market risk, operational risk and funding risk. From the finding, the researcher had made observation at the company about the risk management practices with theory. Researcher also finds the gap between bank exercises with theory related. For recommendation, organization should work together with the organization to conduct the solutions and risk mitigate with bank to get a better performance and increase the bank qualities.